2008
DOI: 10.1103/physreve.77.025101
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic failure in amorphous solids via a cavitation instability

Abstract: The understanding of dynamic failure in amorphous materials via the propagation of free boundaries like cracks and voids must go beyond elasticity theory, since plasticity intervenes in a crucial and poorly understood manner near the moving free boundary. In this Letter we focus on failure via a cavitation instability in a radially-symmetric stressed material, set up the free boundary dynamics taking both elasticity and visco-plasticity into account, using the recently proposed athermal Shear Transformation Zo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…This is understood as significantly higher rate of deformation is developed above the cavitation threshold, where unbounded growth takes place [14], compared to below the threshold where the rate of deformation vanishes at a finite time. We note that the dependence of χ ∞ onD pl affects both the zeroth and first order solutions such that R (0) and R (1) increase.…”
Section: B the Effect Of The Rate Dependence Of χ∞mentioning
confidence: 99%
See 1 more Smart Citation
“…This is understood as significantly higher rate of deformation is developed above the cavitation threshold, where unbounded growth takes place [14], compared to below the threshold where the rate of deformation vanishes at a finite time. We note that the dependence of χ ∞ onD pl affects both the zeroth and first order solutions such that R (0) and R (1) increase.…”
Section: B the Effect Of The Rate Dependence Of χ∞mentioning
confidence: 99%
“…The application of the full fledged theory of STZ to crack propagation is still daunting (although not impossible) due to the tensorial nature of the theory and the need to deal with an extremely stiff set of partial differential equations with a wide range of time-scales and length-scales involved. For that reason it seemed advantageous to apply the full theory to a situation in which the symmetries reduce the problem to an effectively scalar theory; this is the problem of a circular cavity developing under circular symmetric stress boundary conditions [13,14]. While this problem does not reach the extreme conditions of stress concentration that characterizes a running slender crack, it still raises many physical issues that appear also in cracks, in particular the give-and-take between elasticity and plasticity, the way stresses are transmitted to moving boundaries (in apparent excess of the material yield stress) and most importantly for this paper, the possible existence of dynamical instabilities of the moving free boundary.…”
Section: Introductionmentioning
confidence: 99%
“…These studies observed evidence of the curvature dependence of the surface energy on the measured cavitation rate, an effect that has itself been the subject of a significant amount of study [19][20][21][22]. One particularly notable contribution from simulation was the mapping out of the point at which the gas-liquid spinodal dips below the glass line and the glass must become unstable to cavitation [23].Continuum mechanics approaches to modeling the kinetics of cavitation have been developed over many years by numerous researchers [6,[24][25][26][27][28][29][30]. Often preexisting cavities are assumed to exist due to voids, inclusions, or intersections of grains, and the effect of surface energy is neglected.…”
mentioning
confidence: 99%
“…Continuum mechanics approaches to modeling the kinetics of cavitation have been developed over many years by numerous researchers [6,[24][25][26][27][28][29][30]. Often preexisting cavities are assumed to exist due to voids, inclusions, or intersections of grains, and the effect of surface energy is neglected.…”
mentioning
confidence: 99%
See 1 more Smart Citation